New times for migrants' health in Europe - J.M. Reyes-Uruena; T. Noori; A. Pharris; J.M. Jansà (Sociedad Española de Sanidad Penitenciaria, 2014)
Patterns of migration can change greatly over time, with the size and composition of migrant populations reflecting both, current and historical patterns of migration flows. The recent economic crisis has caused a decrease on migration flows towards the most affected areas, as well as cut offs in health interventions addressed to migrants. The objective of this paper is to review available data about interventions on migrants' health in Europe, and to describe changes in migrant health policies across Europe after the economic crisis, that can have a negative effect in their health status. Although migrants have the right to health care under legal settlements issued by the EU, there is no a standard European approach to offer health care to migrants, since; policies in each EU Member State are developed according to specific migrant experience, political climate, and attitudes towards migration. Migrants use to face greater health problems and major health care access barriers, compared with their counterparts from the EU. Therefore, migrant health policies should focus in protects this vulnerable group, especially during economic hardship, taking into account economic and socio-demographic risk factors. There is an especial need for research in the cost-effectiveness of investing in the health care of the migrant population, demonstrating the benefit of such, even in the health of the European native population, and the need for constant intervention despite of resource constraints.